Plasma Epstein-Barr Virus-Deoxyribonucleic Acid Copy Number Predicts Disease Progression in Stage I–III Pulmonary Lymphoepithelioma-Like Carcinoma - Li, Qi-Wen; Qiu, Bo; Hu, Wan-Ming; Guo, Su-Ping; Wu, Ying-Jia; Zhu, Yu-Jia; Hu, Nan; Ai, Xin-Lei; Chen, Nai-Bin; Guo, Jin-Yu; Hu, Yong-Hong; Liu, Meng-Zhong; et al. (Frontiers in Oncology, 2020)
Purpose: To investigate the predictive values of plasma Epstein-Barr Virus (EBV)- deoxyribonucleic acid (DNA) copy number on disease progression and survival in stage I-III pulmonary lymphoepithelioma-like carcinoma (LELC). Patients and Methods: Patients with pathologically confirmed, initially diagnosed or locally recurrent stage I-III pulmonary LELC, who received locally radical treatment and had plasma EBV-DNA results, were retrospectively reviewed. Risk factors of progression-free survival (PFS) and overall survival (OS) were assessed, including the predictive value of pre- and post-treatment EBV-DNA levels. The EBV-DNA change during follow-up was analyzed to determine its association with tumor progression and survival. Results: A total of 102 patients were included in analysis. Eighty-eight patients had initially-diagnosed and 14 had locally recurrent disease. There were 33 patients treated with radical surgery, 55 with definite radiotherapy and 14 with both. EBV-DNA was tested pre-treatment (N = 66), post-treatment (N = 93) and/or during follow-up (N = 58). Forty-one patients had complete EBV-DNA results of all three time points. The overall 2-year PFS and OS were 66.3 and 96.0%, respectively. Pre-treatment EBV-DNA copy number > 10,000 copies/mL was a risk factor of PFS (2-year PFS, > 10,000 vs. ≤ 10,000 copies/mL, 37.2 vs. 75.1%, p = 0.007). Positive post-treatment EBV-DNA also indicated a worse PFS in univariable (2-year PFS, > 0 vs. 0 copy/mL, 25.6 vs. 76.8%, p < 0.001) and multivariable analysis (HR = 3.44, 95% CI, 1.52–7.78; p = 0.003). In the follow-up set, an increasing EBV-DNA exceeding 1,000 copies/mL strongly predicted disease progression within 3 months, with a specificity of 97.5% (95% CI: 86.8–99.6%) and was associated with impaired OS (2-year OS, > 1,000 vs. ≤ 1,000 copies/mL, 72.9 vs. 100%, p < 0.001). Conclusions: Regular testing of EBV-DNA is suggested for pulmonary LELC to predict disease progression. If EBV-DNA copy number was increasing and beyond 1,000 copies/mL during follow-up, intensive radiologic evaluations are recommended.